Sistem Absensi Cerdas Menggunakan Open CV Berbasis Pengenalan Wajah - Afrizal Zein (Institut Sains dan Teknologi Nasional, 2023)
Abstract The face is an important part of the human body uniquely identify a person. Using facial characteristics as biometrics, facial recognition systems can be implemented. That the most demanding task in any organization is marking attendance. In the traditional attendance system, students are summoned byteachers and their presence or absence marked accordingly. However, this traditional technique is time consuming and boring. In this project, Open CV is based on face recognition approach has been proposed. This model integrates a camera captures the input image, an algorithm for detecting the face of a input images, encoding and identifying faces, tagging presence in a spreadsheet and convert it to a PDF file. That the training database is created by training the system with faces from authorized students. The cropped image is then saved as a database with their respective labels. The features are extracted using the LBPH algorithm. Keywords: LBPH, , Attendance, Biometric, Face Recognition